2000
DOI: 10.1096/fj.99-0965com
|View full text |Cite
|
Sign up to set email alerts
|

Decreased fatty acid synthesis due to mitochondrial uncoupling in adipose tissue

Abstract: Synthesis of fatty acid (FA) in adipose tissue requires cooperation of mitochondrial and cytoplasmic enzymes. Mitochondria are required for the production of ATP and they also support the formation of acetyl-CoA and NADPH in cytoplasm. Since cellular levels of all these metabolites depend on the efficiency of mitochondrial energy conversion, mitochondrial proton leak via uncoupling proteins (UCPs) could modulate FA synthesis. In 3T3-L1 adipocytes, 2,4-dinitrophenol depressed the synthesis of FA 4-fold while in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
79
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 53 publications
(100 reference statements)
11
79
0
Order By: Relevance
“…When (post)prandial plasma levels of NEFA and triacylglycerol (TG) exceed the storage capacity of WAT [1], other tissues including the liver and muscle become overloaded with lipids, which results in insulin resistance, the key event in the pathophysiology of metabolic syndrome [2]. The important role of WAT in energy homeostasis is underscored by the findings that WAT is one of the key organs affected by calorie restriction, the most effective strategy to prolong a healthy life in several species [3], and by the fact that accumulation of body fat can be reduced through upregulation of lipid catabolism in WAT [4][5][6][7][8][9][10]. The metabolism and secretory functions of WAT are also modulated by longchain (LC) n-3 polyunsaturated fatty acids (PUFA), namely eicosapentaenoic acid (EPA; 20:5 n-3) and docosahexaenoic acid (DHA; 22:6 n-3), which exert numerous beneficial effects on health, including improvements in lipid metabolism and prevention of obesity and diabetes [11], while decreasing the rate of fatal coronary heart disease in diabetic patients who have had a myocardial infarction [12].…”
Section: Introductionmentioning
confidence: 99%
“…When (post)prandial plasma levels of NEFA and triacylglycerol (TG) exceed the storage capacity of WAT [1], other tissues including the liver and muscle become overloaded with lipids, which results in insulin resistance, the key event in the pathophysiology of metabolic syndrome [2]. The important role of WAT in energy homeostasis is underscored by the findings that WAT is one of the key organs affected by calorie restriction, the most effective strategy to prolong a healthy life in several species [3], and by the fact that accumulation of body fat can be reduced through upregulation of lipid catabolism in WAT [4][5][6][7][8][9][10]. The metabolism and secretory functions of WAT are also modulated by longchain (LC) n-3 polyunsaturated fatty acids (PUFA), namely eicosapentaenoic acid (EPA; 20:5 n-3) and docosahexaenoic acid (DHA; 22:6 n-3), which exert numerous beneficial effects on health, including improvements in lipid metabolism and prevention of obesity and diabetes [11], while decreasing the rate of fatal coronary heart disease in diabetic patients who have had a myocardial infarction [12].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, expression of ectopic UCP1 resulted in reduced expression of genes characteristic of differentiated energy-storing adipocytes, such as peroxisome proliferator-activated receptor gamma (PPARc) and aP2 , in analogy with the induction of ''fat burning adipocytes'' in response to leptin treatment in rats (Zhou et al 1999). In accordance, mitochondrial uncoupling in adipocytes in vitro led to lower intracellular ATP concentrations (Yamada et al 2006;Si et al 2009), up-regulation of glycolysis and mitochondrial biogenesis, and down-regulation of energyconsuming pathways such as fatty acid synthesis (Rossmeisl et al 2000;Si et al 2009;Senocak et al 2007), while lactate production was increased (Rossmeisl et al 2000; ) N D Decreased (Ishigaki et al 2005) Mitochondrial biogenesis and/or content Increased (Rossmeisl et al 2002) Content decreased (Han et al 2004) N D Mitochondrial ROS production ND Reduced (Keipert et al 2010) N D Cellular ATP levels Decreased Yamada et al 2006); increased AMP/ATP ratio Unchanged (Li et al 2000) or decreased (Li et al 2000;Couplan et al 2002;Han et al 2004 Rossmeisl et al, unpublished) suggested an upregulation of lipid catabolism in SM of high-fat diet-fed mice in response to the transgenic UCP1 expression in WAT, which is also associated with hypolipidemic effects, especially under fasted conditions. The effect of UCP1 expression on SM phenotype was studied in detail by Couplan et al (2002), who reported a fiber type switch from fast glycolytic fibers to slow oxidative fibers in gastrocnemius and plantaris muscle accompanied by a reduced muscle mass.…”
Section: Metabolic Effects Of Ectopic Ucp1 At Cellular and Tissue Levelsmentioning
confidence: 96%
“…That mitochondrial uncoupling in WAT could reduce obesity was found in 1995 by Kopecky et al (1995) using aP2-Ucp1 transgenic mice and explored systematically later on (Kopecky et al 1996a, b;Stefl et al 1998;Baumruk et al 1999;Rossmeisl et al 2000Rossmeisl et al , 2002Rossmeisl et al , 2005Flachs et al 2002;Matejkova et al 2004). In these mice, the fatspecific aP2 promoter was used to drive expression of UCP1 from the whole genomic DNA sequence, resulting in enhanced expression of UCP1 in both WAT and BAT of mice with C57BL/6 J background.…”
Section: White Adipose Tissuementioning
confidence: 99%
See 2 more Smart Citations